2023
DOI: 10.1590/1678-4324-2023210726
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Dietary Wheat and Corn Glutens on the Histopathological and Immunohistochemical Structure of the Ovarian Tissue and Serum and Ovarian Tissue LH and FSH Levels and Lipid Profiles in Rats

Abstract: This study was aimed at determining the effects of corn and wheat glutens on the histopathological and immunohistochemical structure of the ovarian tissue, luteinizing hormone (LH) and follicle-stimulating hormone (FSH) levels, and lipid profile in rats. Twenty-day-old 24 female Sprague-Dawley rats were assigned to three groups, and were raised until 185 days of age. Three study groups, named as Wheat, Corn and Soybean Groups, were established and fed on wheat gluten, corn gluten and soybean meal, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…On the other hand, Imik et al. ( 2023 ) reported that wheat gluten fed from 21 days of age to 185 days of age resulted in an increase in FSH levels of serum tissue and LH levels of ovarian tissue in the groups fed corn gluten and soybean meal, whereas FSH and LH levels of ovarian tissue were not influenced. In our study, serum FSH levels were significantly higher in Control G than in Wheat G and Corn G, whereas LH levels were similar between the groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, Imik et al. ( 2023 ) reported that wheat gluten fed from 21 days of age to 185 days of age resulted in an increase in FSH levels of serum tissue and LH levels of ovarian tissue in the groups fed corn gluten and soybean meal, whereas FSH and LH levels of ovarian tissue were not influenced. In our study, serum FSH levels were significantly higher in Control G than in Wheat G and Corn G, whereas LH levels were similar between the groups.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that balanced nutrition is very important in the development of the reproductive system (Gumus et al., 2020 ; Imik, 2019 ; Imik et al., 2023 ; Qi et al., 2019 ; Ye et al., 2022 ). Ye et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ab80436, Cambridge, UK). After three washes with 0.1% Tween 20 in PBS, the sections were incubated with 3,3-diaminobenzidine (Dako Cytomation, Glostrup, Denmark) and counterstained with Mayer' s hematoxylin (Dako Cytomation) [12,13].…”
Section: Immunohistochemical Examinationsmentioning
confidence: 99%
“…Degeneration, inflammation and biliary hyperplasia were observed in this study in liver tissue similar to the above findings; it was determined that the degeneration parameter increased only in the Wheat group while disease was thought to only affect the intestines in previous studies. However, in recent studies, it has been reported that the disease also affects organs such as the liver, skin, brain and ovarian [13,15]. For this reason, it is observed that celiac disease causes multiple organ disorders [16].…”
Section: Immunohistochemical Findings In Liver Tissuementioning
confidence: 99%